Pengaruh Identitas Etnis Politik Terhadap Perilaku Pemilih: (Studi Kasus Pemilihan Walikota Dan Wakil Walikota Medan Tahun 2020) - Kahirunnisyah Nasution; Herti Noita Simbolon; Maida Puspa Ristika Ambarita; Julia Ivanna (Public Service and Governance Journal, 2024)
This research is entitled The influence of ethnic identity politics in the election of Mayor and Deputy Mayor of Medan 2020. What will be studied in this research is to see the involvement of ethnic identity politics in the election of Mayor and Deputy Mayor of Medan 2020. This research uses political anthropology methods with a functionalist approach where the approach This is built on ethnic lineages which allow for political relations with ethnic groups and organizations. Data collection techniques were carried out using in-depth interview techniques, observation and documentation. Meanwhile, the data analysis technique in this research uses qualitative descriptive data analysis. The technique for determining informants in this research is Purposive Sampling, where the selection of informants is chosen deliberately based on predetermined criteria, namely people who experience and feel directly the influence exerted by candidate pairs using ethnic identity. So the informants in this research were people living in Medan Perjuangan, namely 10 informants, namely 2 people each from the Malay, Javanese, Batak, Acehnese ethnicities, and 2 people from the Chinese ethnicity. The research results show that political ethnic identity does have an influence, but the people of Medan also consider other factors in determining their choices. Full community participation in elections is related to awareness of the importance of community contributions, while the assessment of candidates is not only focused on ethnic identity, but involves performance, vision and mission and leadership behavior. Overall, the results of this study indicate that while political ethnic identity is not an important factor, the people of Medan prefer to understand and evaluate candidates based on performance and leadership criteria.